Design, synthesis and biological evaluation of novel nicotinamide derivatives bearing a substituted pyrazole moiety as potential SDH inhibitors. Issue 8 (2nd January 2017) - Lv, Xian‐Hai; Ren, Zi‐Li; Liu, Peng; Li, Bing‐Xin; Li, Qing‐Shan; Chu, Ming‐Jie; Cao, Hai‐Qun
Abstract: BACKGROUND: Succinate dehydrogenase (SDH) plays an important role in the Krebs cycle, which is considered as an attractive target for development of succinate dehydrogenase inhibitors (SDHIs) based on antifungal agents. Thus, in order to discover novel molecules with high antifungal activities, SDH as the target for a series of novel nicotinamide derivatives bearing substituted pyrazole moieties were designed and synthesised via a one‐pot reaction. RESULTS: The biological assay data showed that compound3 l displayed the most potent antifungal activity with EC50 values of 33.5 and 21.4 µm against Helminthosporium maydis and Rhizoctonia cerealis, respectively. Moreover, 3 l exhibited the best inhibitory ability against SDH enzymes. The results of docking simulation showed that3 l was deeply embedded into the SDH binding pocket, and the binding model was stabilised by a cation–π interaction with Arg 43, Tyr 58 and an H‐bond with Trp 173. CONCLUSION: The study suggests that the pyrazole nicotinamide derivative3 l may serve as a potential SDHI that can be used as a novel antifungal agent, and provides valuable clues for the further design and optimisation of SDH inhibitors. © 2016 Society of Chemical Industry